1974
DOI: 10.1086/152893
|View full text |Cite
|
Sign up to set email alerts
|

The Fokker-Planck Coefficient for Pitch-Angle Scattering of Cosmic Rays

Abstract: most cases has been evaluated incorrectly in the past. For example, there is no formal justification for the approximations due to Jokipii (1966, 1971), which permit this integral to be expressed simply in terms of a one-dimensional power spectrum of magnetic field fluctuations, evaluated at a resonant wavenumber. By using both analytic and numerical techniques, we correctly evaluate <(AP2) >/At for a general form of the power spectrum, which should provide a good fit to observed power spectra. In the limit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 9 publications
3
51
0
Order By: Relevance
“…More recently, that picture has been put into question by our finding that for electrons, PA scattering is actually fastest across μ = 0 (where μ is a gyration-averaged PA cosine μ or μ av ; Ragot 1999Ragot , 2005see Figures 3-5 of Ragot 2006a) and does not obey a diffusive law. This is consistent with the earlier finding that the Fokker-Planck PA scattering coefficient, calculated for a finite gyroradius, contains a Dirac δ function in μ (Fisk et al 1974;Klimas & Sandri 1973), further confirmed by Goldstein et al (1975) and related to mirroring. The extent of the nondiffusive time variations of μ, however, is much broader than ever anticipated.…”
Section: Introductionsupporting
confidence: 93%
“…More recently, that picture has been put into question by our finding that for electrons, PA scattering is actually fastest across μ = 0 (where μ is a gyration-averaged PA cosine μ or μ av ; Ragot 1999Ragot , 2005see Figures 3-5 of Ragot 2006a) and does not obey a diffusive law. This is consistent with the earlier finding that the Fokker-Planck PA scattering coefficient, calculated for a finite gyroradius, contains a Dirac δ function in μ (Fisk et al 1974;Klimas & Sandri 1973), further confirmed by Goldstein et al (1975) and related to mirroring. The extent of the nondiffusive time variations of μ, however, is much broader than ever anticipated.…”
Section: Introductionsupporting
confidence: 93%
“…In the recent paper of Yan and Lazarian (2008, henceforth YL08), a nonlinear theory (NLT) based on the Völk (1975) suggestion was developed. The new formalism was applied to two major processes of CR acceleration in turbulence, namely, to gyroresonance and to the transient time damping (TTD) Fisk et al (1974); Goldstein et al (1975).…”
Section: Second Order Fermi Acceleration and Turbulencementioning
confidence: 99%
“…Introduction in many areas of 5nlar wind research it is common to assume, explicitly or implicitly, that the medium being studied is either tin y stationary or spatially homogeneous (or both). For example, the thoories of pitch angle scattering of charged particles (Jokipii, 19603;Ftall anO Sturrock, 1967;Hasselmann and Wibberenz, 1968;Klimas and Sandri, 1971;,zones, Kaiser and Birmingham, 1973;Fisk et al, 1974] and field line random walk (dokipii, 1966;J'okipii andParker, 1968, 1969;jokipii, 1971) both utilize the concept of an ensemble average of the interplanetary mag netic fields. Such averages are meaningful only if a particular realization of the magnetic field time series does, in fact, represent a realization of a stationar y process.…”
mentioning
confidence: 99%